UJI DIAGNOSTIK ICE PACK TEST DAN REPETITIVE NERVE STIMULATION SERTA KOMBINASINYA PADA MIASTENIA GRAVIS - Winnugroho Wiratman; Bazzar Ari Mighra; Fitri Octaviana; Astri Budikayanti; Luh Ari Indrawati; Triana Ayuningtyas; Ahmad Yanuar Safri; Manfaluthy Hakim (PERDOSNI, 2021)
Introduction: Diagnosis of myasthenia gravis (MG) is based on clinical symptoms, physical examination and supporting examination; so far, no examination has become the primary standard in the enforcement of MG. Supporting examinations that are fast, non-invasive and easy to do are ice pack test (IPT) and repetitive nerve stimulation (RNS). Aims: To find the sensitivity and specificity of the IPT, RNS examination, and the combination of both in enforcing the diagnosis of MG. Methods: This study was conducted with a cross-sectional design using primary data and medical records of suspicious MG patients with ptosis in Cipto Mangunkusumo General Hospital between July-November 2019. Results: Of the 38 subjects with ptosis, 35 subjects were confirmed MG with positive SF-EMG/AChR antibodies/response therapy. The ice pack test was positive in 29 subjects (76.3 %). The diagnostic test results of the ice pack test have sensitivity 80%, Specificity 66.67%, area under the curve (AUC) value of 73.3%, the RNS has a sensitivity of 60%, specificity 100%, AUC value 80%, while the combination test has sensitivity 94.28%, specificity 66.67% and AUC value 80.5%. Discussion: The combination of IPT and RNS has good diagnostic value so it can be used as a supporting examination to the diagnosis of MG. Keywords: diagnostic test; ice pack test; myasthenia gravis; ptosis; RNS